Actualization of Music-Folklore Knowledge in Education Creative Personality of the Future Music Teacher - Yakivchuk, Halyna; Vroda, Lyudmyla (Pedagogical Discourse, 2012)
The article reveales the substantive content of the discipline "Folk music of Ukraine" and the current issues of efficiency and feasibility of the course in the process of education and professional training of the future music teacher. The author reveals the specific charcter of the discipline and mandatory practice and laboratory work, aimed at education and development of the creative qualities of the future music teacher (originality of thinking, sociability, reflection, self-organization, empathy, persistence, etc.) and the capacity for creative self-organization, self-improvement.